Dens Evaginatus: A Problem-Based Approach. (8th December 2015) - Ayer, A.; Vikram, M.; Suwal, P.
Abstract : Dens evaginatus is an uncommon developmental anomaly of human dentition characterized by the presence of tubercle on the occlusal surface of mandibular premolars and lingual surface of anterior teeth. Due to occlusal trauma this tubercle tends to fracture thus exposing the pathway to the pulp chamber of teeth. This case report is about the presentation of dens evaginatus in mandibular premolars bilaterally; among them tooth 44 was associated with chronic apical periodontitis. Fractured tubercle of three premolars was sealed with composite resin. Root canal treatment was performed with tooth 44. Routine endodontic treatment did not result in remission of infection. Therefore, culture and sensitivity tests were performed to identify the cause and modify treatment plan accordingly. Triple antibiotic paste was used as an intracanal medicament to disinfect the root canal that resulted in remission of infection.